2015
DOI: 10.1590/1516-4446-2014-1389
|View full text |Cite
|
Sign up to set email alerts
|

Sports practices related to alcohol and tobacco use among high school students

Abstract: Objective: To examine the relationship between alcohol and tobacco use and sports in a national sample of secondary students. Methods: This cross-sectional study enrolled a representative sample of secondary students from public and private schools from all 27 Brazilian state capitals. Students were assessed in 2010 by a self-report questionnaire including questions on drug use and sport activity in the last month (n=13,872). Results: Subjects who played sports exhibited a higher frequency of alcohol use and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 33 publications
(49 reference statements)
2
17
0
6
Order By: Relevance
“…The importance of health-related behaviors in the practice of PA is also highlighted. Fernandes et al 10 revealed that the increase in PA is associated with healthy eating habits while Bedendo and Noto 11 reported an increase in alcohol consumption associated with this practice.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of health-related behaviors in the practice of PA is also highlighted. Fernandes et al 10 revealed that the increase in PA is associated with healthy eating habits while Bedendo and Noto 11 reported an increase in alcohol consumption associated with this practice.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it may logically be expected that children who are involved in sports would be less likely to smoke [32]. However, the results of studies that have examined the association between engagement in sports and smoking in adolescence have not been consistent [32,33,34]. More precisely, when investigations have compared athletes and non-athletes, the prevalence of smoking was found to be lower in adolescents actively involved in sports [33,35].…”
Section: Introductionmentioning
confidence: 99%
“…In those studies, a relationship between PA and alcohol use was shown. This relationship was observed in both directions and different types of PA [ 10 , 29 , 36 , 40 , 41 , 50 , 51 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 89%